1980
DOI: 10.1111/j.1745-6584.1980.tb03366.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐Water Tracers — A Short Review

Abstract: Tracers are used widely to determine the direction and velocity of ground‐water movement. Failures of tracer tests are most commonly a result of incorrect choice of tracers, insufficient concentrations of tracers, and a lack of an understanding of the hydrogeologic system being tested. Some of the most useful general tracers are bromide chloride, rhodamine WT, and various fluorocarbons. For certain purposes, dyed clubmoss and baker's yeast have proved valuable. Many radionuclides including 3H, 82Br, and 198Au … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
155
0
9

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(165 citation statements)
references
References 17 publications
1
155
0
9
Order By: Relevance
“…In both Exp 1 and 2, uranine was used as the tracer, which is a fluorescent, non-toxic, organic compound that belongs to the category of xanthene dyes (Davis et al, 1980;Flury and Wai, 2003). To reduce background fluorescence from organic substances like humic and fulvic acids, and to avoid adsorption onto the organic matter coating of sediment particles, clean construction sand was used.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In both Exp 1 and 2, uranine was used as the tracer, which is a fluorescent, non-toxic, organic compound that belongs to the category of xanthene dyes (Davis et al, 1980;Flury and Wai, 2003). To reduce background fluorescence from organic substances like humic and fulvic acids, and to avoid adsorption onto the organic matter coating of sediment particles, clean construction sand was used.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Br-is commonly used as a groundwater tracer because it has relatively low toxicity, usually exists at low concentrations in the environment, and is simple to measure, inexpensive, and assumed to be conservative [Davis et al, 1980]. The last is believed because soils and sediments are thought to have a negative surface charge that repels the negatively charged Brions, thus limiting interaction with the solid phase of porous media.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of multiple tracers should alleviate many of the complexities associated with assessing groundwater in the system. Many studies have utilized natural geochemical tracers to quantify groundwater in coastal systems [Cable et al, 1996a;Moore, 1998;Corbett et al, 2000;Top et al, 2001;Charette and Buesseler, 2004], which are found in elevated concentrations relative to surface waters [Davis et al, 1980]. This study incorporates 222 Rn and 4 He/ 3 He/ 3 H as natural tracers of groundwater.…”
mentioning
confidence: 99%